Lifelong learning in inclusive schooling at european level - Núñez Angulo, Beatriz F.; Santamaría Conde, Rosa Mª (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This work arises from the European project “European Diversity Design for Inclusive Education”, EURODDIP-e, (2018-1-ES01-KA291-050300. The aim is to obtain information on the needs of teachers to include students in their classrooms and to make proposals for evaluation and intervention. The methodology is based on the design and application of the QT questionnaire [http://hdl.handle.net/10259/5262], with α= 0.83 and n= 1.212 teachers in Primary Education in European countries. The results coincide and, in some items, differ from those of other research. In conclusion, the data support the importance and need to continue working on teacher support for educational inclusion.